Evidence of intimal tear in type A intramural hematoma of the aorta: A case series. (2018) - Filippone, Gianfranco; Caruana, Giovanni; Calia, Claudia; Moscaritolo, Violetta; Argano, Vincenzo
Highlights: We report two cases of type A intramural hematoma of the aorta. We found radiological and intraoperative evidence of an intimal tear. This finding supports the hypotesis that IMH belong to "aortic dissection" disease. Abstract: Introduction: Aortic intramural hematoma (IMH) is described as "dissection without intimal tear" due to rupture of vasa vasorum, which results in bleeding within the tunica media in the absence of intimal disruption or blood flow communication. The aim of our study is to validate perioperative evidence of intimal entry tear in patients with IMH and to suggest that this entity may represent a part of a disease and not a separate disease. Presentation of cases: We report two patients admitted to our institution with sudden onset thoracic pain. A CT scan showed an aneurysm of the ascending aorta complicated by type A IMH. The patients underwent open operation. Surgical set-up has included right axillary artery as arterial inflow, no cross-clamp before hypothermic circulatory arrest and Kazui protocol for selective antegrade cerebral perfusion. We found no evidence of intimal flap, but we identified an intimal tear in both patients. A hemiarch procedure associated with root replacement, using two-grafts techniques was performed in both cases. The postoperative course was uneventful and the patients were discharged home. Discussion: Recent data are emerging from the radiologic literature about the evidence of intimal lesions in IMH, but surgical reports are scant. The evidence of intimal tears contributes to consider as questionable the etiological role of vasa vasorum and it may justify updates in the management. Conclusion: We consider that IMH may represent a part of a disease (aortic dissection), depicted by radiological images in a specific single instant of its clinical evolution.